1992
DOI: 10.1002/app.1992.070450810
|View full text |Cite
|
Sign up to set email alerts
|

Buffer effects on aqueous swelling kinetics of polyelectrolyte gels

Abstract: Electrolytes are often added to a gel‐swelling medium under the assumption that the important conditions which characterize swelling rates are the solution pH and ionic strength, with little emphasis on the nature of the electrolyte. Previous research by Siegel et al. has indicated that the presence of the un‐ionized acidic form of an electrolyte buffer is a primary rate determinant for swelling of a polybase gel. A systematic swelling study on two separate gels, 2‐hydroxyethyl methacrylate copolymerized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 27 publications
2
41
1
Order By: Relevance
“…Similar effects of salt chemistry on gel swelling have been reported earlier (23,24) Partitioning of CrCVD Anions Figure 3 presents experimental data for the partition coefficients of Cr(VI) into NIPA/MAPTAC gels of 0-3% CM in aqueous potassium dichromate solutions at 22°C. Data also appear in Table 2.…”
Section: Partitioning Measurementssupporting
confidence: 75%
“…Similar effects of salt chemistry on gel swelling have been reported earlier (23,24) Partitioning of CrCVD Anions Figure 3 presents experimental data for the partition coefficients of Cr(VI) into NIPA/MAPTAC gels of 0-3% CM in aqueous potassium dichromate solutions at 22°C. Data also appear in Table 2.…”
Section: Partitioning Measurementssupporting
confidence: 75%
“…2(a) and 2(b) were used in the calculation as the boundary conditions for Eq. (15) and as the function f for Eq. (16), respectively.…”
Section: ) Analysis Of the Swelling Ratementioning
confidence: 99%
“…[5][6][7][8][9] In recent Contract grant sponsor: National Natural Science Foundayears, it was found that some of the polymer comtion of China.…”
Section: Introductionmentioning
confidence: 99%